Implementation of the MBKM Curriculum (Independent Learning Independent Campus) Towards the Islamic Religious Education Study Program at Higher College Level - SM, Khairatunnimah.; Sari, Reni Puspita; Solihah, Arifatus (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Universities have so far implemented a credit learning system which is almost entirely dependent on classroom learning. This shows the low level of learning independence for students. Therefore, the idea of “Independent Learning Independent Campus” emerged, or